Análise de crescimento e produção de três genótipos de bananeira sob diferentes doses de biossólido nas condições edafoclimáticas de São Luís – Maranhão - Souza, Cláudio Marcelo de (2007)
This work had as objective to evaluate the effect of the application of biossolid originating from the Sewers Treatment Station (ETE) of Jaracaty, located in the island of São Luís - MA, in the manuring of the banana tree (Musa sp.) in substitution to the nitrogen originating from commercial formula of sulfate of ammonium in the environmental conditions of the municipal district of São Luís in Maranhão, Brazil, about the growth and productivity of three banana tree genotypes that have been promoted by Embrapa - Cassava and Fruticulture National Center (CNPMF) as capable to provide more productive and less susceptible to diseases and curses cultivations. The chosen genotypes for the comparisons of this experiment were the Pacovan Ken, the Thap Maeo and the Caipira. A block randomized drawing was installed in portions subdivided with the three genotypes, five treatments and three replication, in area belonging to INPE – National Institute of Space Researches, next to the Technological Nucleus of Rural Engineering of the State University of Maranhão. The plants were analyzed, with the intervals of 30 days starting from the thirtieth day after the planting of the seedlings, the diameter of the pseudosterm, the plant-mother's height, the number of active leaves, the foliar area of the third leaf and the number of children emitted as parameters of growth. For occasion of the crop of the bunch, it was also analyzed the number of days from the planting to the crop, the number of fruits for bunch, and the medium weight of the bunch. For all of the studied parameters, the treatment without nitrogen, presented smaller index of growth and productivity to the others. The treatments with different biossolid dosages provided results similar to the obtained with recommended mineral manuring. Would be emphasized the largest dosage (13 ton.ha-1) as that that reached the index best of productivity. Considering the genotypes, it was observed that Caipira presented smaller growth and productivity than the others one. The Thap Maeo genotype presented the larger weight bunch and number of fruits, being revealed the more adapted for the experimental conditions.